Construction of a Questionnaire Evaluating Secondary Education Students’ Knowledge about Rhythmic Gymnastics - Zisi, Βασιλική; Boura, Σοφία; Polatou, Ελιζάνα; Gianitsopoulou, Ευγενία; Kioumourtzoglou, Ευθύμης (Inquiries in Physical Education and Sport, 2009)
Rhythmic Gymnastics (RG) is a spectacular Olympic feminine sport but not widely known in the public. The evaluation complexity of each competition renders difficult the judgment from the public. The aim of the present study was to construct a valid and reliable questionnaire for the evaluation of general and special knowledge about RG, in secondary education students. RG judges and experts were involved in the construction of the initial construction. Two pilot studies were conducted in a sample of 108 students and 53 RG athletes. The participants in the main study were 274 high school students aged 14 – 16 yrs, randomly selected from 7 public high schools in Attica prefecture. Questions with low discrimination index and inappropriate difficulty index (over.90 or under .10) were removed and the final questionnaire consisted of 26 multiple choice questions in 10 thematic units: general elements about RG, apparatus, age and costume of athletes, time duration of programs, types of competitions, composition requirements of programs for the result of judgment (artistic, technical value and execution), rules of team competition (ensemble), and penalties for the errors. The difficulty indexes ranged from .13 to .83 (Μ=.52±.20), while the questions’ discrimination indexes ranged from .21 to .75 (Μ=.35±.12). Alpha cronbach was a=.67. The participants’ score in the main study ranged from 7.41% to 88.89% (Μ=50.05 ± 15.27). In conclusion the final questionnaire is appropriate for the evaluation of high school students’ knowledge about RG in Greek language and it could be useful for the research on RG spectators.